The Labour Party and the Nursing Profession - MacDonald, James Ramsay, 1866-1937 (London : The Labour Party (London : Co-operative Print. Society Ltd.), 1927)
1927 1927 1920s 40 pages 37 SCHOOL NURSES. TRAINING AND QUALIFICATIONS. The qualification most usually demanded from a school nurse is a certificate of three years' general nursing training, although this is not insisted upon by the Board of Education. Some local authorities ask for other certificates in addition, such as the C.M.B. or a health visitor's or school nurse's certificate, and many state that although not essential, preference will be given to candidates holding such certificates in addition to that of general nursing training. In a few cases, school nurses hold the Board of Education Diploma for health visitors, but this is not a usual qualification for a school nurse, unless she is also a health visitor. The new certificate for health visitors, of the Central Examining Body approved by the Ministry of Health, also covers school nursing, part of the syllabus of training in preparation for this examination being devoted to the school medical service. It is not compulsory, however, for school nurses to have this certificate, as in the case of health visitors. Apart from London and some other large provincial towns, health visiting and school nursing are usually combined. In such cases, the qualifications demanded are those of a health visitor. DUTIES. The duties of school nurses include some or all of the following :— 1. Examination of all children for the detection of verminous conditions and minor defects. 2. Weighing, measuring and vision testing of children in certain age groups and assisting the school doctors with routine inspections. 3. Supervision of children excluded from school for contagious skin complaints. 4. Periodic weighing of children who are or have recently been in home contact with a case of tuberculosis, and in whom no tubercular losion has been detected. 5. Some more or less irregular work in connection with infectious diseases, i.e., swabbing or diphtheria contacts and carriers, and the exclusion from school of children with suspicious symptoms during an epidemic of measles. 6. Attending at School Clinics for the carrying out of treatment. This may include assisting at minor operations, e.g., the removal of tonsils and adenoids. 7. Visiting the parents of children after school medical inspection to advise as to the best means of obtaining the treatment prescribed by the doctor, and to suggest any improvements in the general, hygienic conditions which may be practicable. In London, the last of these duties, usually known as " following-up," is done by the members of voluntary Care Committees, few of whom have any special training for the work. Outside London, this is habitually included in the duties of school nurses. There is a strong case for the inclusion of this duty among those performed by school nurses in London. SALARIES AND CONDITIONS OF SERVICE. General speaking, the salaries of school nurses are approximately the same as those of health visitors. Where any difference is made by local authorities employing both kinds of officer, the scale of salaries for school 126/TG/RES/X/1036A/14